Colposcopically directed cervical biopsy during pregnancy; minor surgical and obstetrical complications and high rates of persistence and regression. (17th April 2013) - Kärrberg, Cecilia; Brännström, Mats; Strander, Björn; Ladfors, Lars; Rådberg, Thomas
Abstract Objective To evaluate whether colposcopically directed cervical biopsies during pregnancy are associated with surgical/obstetric complications and to examine the natural course (regression, persistence, progression) of dysplasia during pregnancy. Design Prospective clinical study. Setting and population University Hospital and 251 pregnant women with atypical cervical cytology in early pregnancy. Methods The patients were investigated by colposcopically directed punch biopsies, colposcopically directed loop‐biopsies or LEEP‐cones. The histology results during pregnancy were compared with those after delivery to evaluate the natural course of dysplastic lesions during pregnancies. Postoperative complications were recorded. Obstetric outcome was recorded and compared with the 54 919 other births in the same geographical area during the study period. Main outcome measures Persistence, regression and progression of cervical dysplasia, surgical complications after diagnostic procedure, incidence of preterm birth, mode of delivery. Results Only a minor part (12.3%) of the dysplastic lesions showed progression during pregnancy, with 54.6 and 33.1% showing persistence and regression, respectively. No surgically related postoperative bleeding that needed surgical (diathermy/suture) treatment occurred and the miscarriage rate was low (0.8%). There were no differences in mode of delivery, preterm birth or other obstetrical variables between the study group and the large control cohort. Conclusion Investigation of atypical cytology during pregnancy with biopsy including large loop excisions is a safe procedure with regard to surgical complications and obstetrical outcome. There is a high rate of persistence and regression of dysplasia during pregnancy.